Blood lactate concentrations in ponies and miniature horses with gastrointestinal disease. (4th March 2013) - Dunkel, B.; Kapff, J. E.; Naylor, R. J.; Boston, R.
Summary Reasons for performing study Clinical impression suggested that pony and miniature breeds (collectively referred to as ponies) presenting to a referral hospital for investigation of gastrointestinal disease had higher blood lactate concentrations on admission than large breed horses. Objectives The study tested the hypothesis that ponies with gastrointestinal disease had higher blood lactate concentrations on admission than large breed horses with similar disease severity. Study design Retrospective case–control study. Methods Medical records from September 2006 to July 2011 were reviewed for ponies with a primary presenting complaint of gastrointestinal disease. Two larger breed horses with gastrointestinal disease were selected as controls for each case. Data collected included case details, historical and clinicopathological findings, diagnosis and outcome. Results Information was collected on 50 ponies and 100 horses. Ponies had higher mean ± s.d. respiratory rates (27 ± 13 vs. 21 ± 13 beats/min; P = 0.01) and rectal temperatures (37.9 ± 0.6 vs. 37.4 ± 0.6°C; P = 0.006) and a longer median duration of clinical signs prior to presentation (10 h [1–72 h] vs. 6 h [1–120]; P<0.001). Median blood lactate concentrations on admission were higher in ponies than in horses (2.8 mmol/l [0.7–18.0] vs. 1.6 mmol/l [0.4–8.1]; P = 0.001). All other parameters relating to colic severity were not significantly different between groups, although more horses underwent exploratory laparotomy (19/50 ponies and 55/100 horses; P = 0.05). Median blood lactate concentrations in ponies with large intestinal disease, nonstrangulating lesions, undergoing medical treatment and surviving ponies were significantly higher than in horses in the same category. In contrast to horses, no differences in blood lactate concentrations exist between ponies with medical vs. surgical treatment, strangulating and nonstrangulating lesions and surviving and nonsurviving ponies. Conclusion and potential relevance Ponies might present with higher blood lactate concentrations than horses and might falsely be suspected of having a surgical lesion or a poorer prognosis if veterinarians are not aware of breed differences.